Antibiotic evaluation of the nanocomposites IONs-MWCNTs-Pc and IONs-GO-Pc encapsulated in the biocompatible hydrogel poly(VCL-co-PEGDA) based on photodynamic effect - Coralia Cuadrado; Alex Mantilla; Luis Hidalgo; Diego Punina (Electronic Journal of Biotechnology)
Background: The rise of drug-resistant bacteria, including Staphylococcus aureus and Escherichia coli, presents a significant healthcare challenge. This study focuses on the development of two novel nanocomposites IONs-MWCNTs-Pc and IONs-GO-Pc encapsulated within a biocompatible poly(VCL-co-PEGDA) hydrogel. These composites are designed for use in photodynamic therapy and evaluated for their antimicrobial efficacy against resistant pathogens. Results: The synthesized nanocomposites, when irradiated with red light at 630 nm, showed significant antimicrobial activity, resulting in a marked reduction in the viability of S. aureus ATCC 27543, S. aureus ATCC 33591, and E. coli ATCC 971182. Photodynamic studies demonstrated that the IONs-GO-Pc nanocomposite was more efficient in generating singlet oxygen compared to IONs-MWCNTs-Pc, which correlated with its superior antimicrobial performance. Structural and chemical characterization confirmed the successful incorporation of nanomaterials and photosensitizers, enhancing the photodynamic effect. Conclusions: The study demonstrates that both IONs-MWCNTs-Pc and IONs-GO-Pc nanocomposites show promise as alternative treatments for infections caused by antibiotic-resistant bacteria, with the GO-based composite showing higher photodynamic therapy efficacy. These findings suggest that such nanocomposites could play a pivotal role in advancing antimicrobial strategies against resistant pathogens.How to cite: Cuadrado C, Mantilla A, Hidalgo L, et al. Antibiotic evaluation of the nanocomposites IONs-MWCNTs-Pc and IONs-GO-Pc encapsulated in the biocompatible hydrogel poly(VCL-co-PEGDA) based on photodynamic effect. Electron J Biotechnol 2025;73. https://doi.org/10.1016/j.ejbt.2024.08.002.